Angiodysplasia of the Gallbladder: An Unknown Risk Factor for Cholecystolithiasis - Ivan Švagelj; Mirta Vučko; Mato Hrskanović; Dražen Švagelj (Case Reports in Pathology)
Angiodysplasia is a common type of lesion characterized by malformed submucosal and mucosal blood vessels. Angiodysplasia of the gallbladder is extremely rare, usually an incidental finding, with only two cases reported. Laparoscopic cholecystectomy is a curative treatment for angiodysplasia of the gallbladder. Our report describes a case of angiodysplasia of the gallbladder in a patient who underwent elective laparoscopic cholecystectomy for biliary colic because of gallstones, and a systematic literature review. We surmise that angiodysplasia of the gallbladder could be a risk factor for gallstones in younger female patients.